Significance of Financial Indicators and Banks’ Credit Ratings During Crisis - Chodnicka-Jaworska, Patrycja (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The main aim of the paper is analysis of behaviour of banks’ credit ratings during the boom and economic downturns by taking account the financial indicators. It has been made a literaturę review, and there have been put the following hypotheses: During the financial crisis it has been observed the stronger impact of the financial indicators. Banks’ notes during the economic downturns are lower than during boom period. To the analysis there have been used quarterly data for 1998–2016 period of time for European banks. To the analysis there have been used quarterly data from 1998–2016. Hypotheses were verified by using the ordered panel probit models for long term issuer credit ratings. The studies show that, during the crisis, Fitch and Moody’s banks’ credit ratings are lower than during the boom. Furthermore, it was noted that S&P’s notes are insensitive to the analysed changes.